Practical application study for food safety risk mitigation in a nut processing facility - Clem, Barbara (Kansas State University, 2018)
Food processing facilities are faced with many challenges in ensuring that the food supply is safe for consumption. Listeria monocytogenes is a food pathogen that has been linked to ready-to-eat foods, including tree nuts. Listeria monocytogenes is part of the ubiquitous microorganism genus, Listeria. The most likely cause of Listeria contamination in food is post-processing contamination. The purpose of this research is to identify and examine possible solutions a nut processing facility might employ to mitigate a food safety risk. The outcome of this research helps to establish the most financially viable method a processing facility may implement to address and mitigate an established risk given defined premise construction and constraints. The research objective is to identify a solution, implement a course of action, and establish safeguards to prevent recurrence of the issue. Factoring in facility specific variables as well as industry data and relevant analyses, the research conducted concludes with recommended actions for the facility to make, including a combination of structural design changes coupled with extensive chemical sanitation techniques.
Keywords: Listeria; Food safety; Food processing; Bacteria; Pathogen; Cost